2012
DOI: 10.1590/s1516-35982012000600016
|View full text |Cite
|
Sign up to set email alerts
|

Selection for higher body weight in Nelore cattle is effective in achieving an increase of longissimus muscle area without reducing subcutaneous fat thickness

Abstract: -The objectives of this study were to estimate heritabilities and genetic and phenotypic correlations between carcass traits measured by ultrasound and other economically important traits generally used as selection criteria in beef cattle and to estimate the genetic changes in the carcass traits as a result of selection for post-yearling weight. Carcass traits measured by ultrasound at two ages (12 and 18 months) and the correlation of these traits with weight, hip height and body condition score of males (ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
2
7
1
Order By: Relevance
“…Table 3 shows the results of descriptive statistics for variance and heritability estimates of growth, fertility, and carcass traits obtained by two-trait analysis with TOP5. For some traits, heritability estimates were higher than those reported for Nellore herds, whereas heritability for HH was similar (Cyrillo et al, 2001;Magnabosco et al, 2002;Giannotti et al, 2005;Yokoo et al, 2010;Pinheiro et al, 2012). However, heritability for BW was much higher than estimates reported in previous studies.…”
Section: Resultscontrasting
confidence: 64%
See 3 more Smart Citations
“…Table 3 shows the results of descriptive statistics for variance and heritability estimates of growth, fertility, and carcass traits obtained by two-trait analysis with TOP5. For some traits, heritability estimates were higher than those reported for Nellore herds, whereas heritability for HH was similar (Cyrillo et al, 2001;Magnabosco et al, 2002;Giannotti et al, 2005;Yokoo et al, 2010;Pinheiro et al, 2012). However, heritability for BW was much higher than estimates reported in previous studies.…”
Section: Resultscontrasting
confidence: 64%
“…This may be beneficial because these traits show a favorable genetic and phenotypic correlation with carcass weight (Bonilha et al, 2008). However, genetic gain in HH, which is also genetically correlated with TOP3 and TOP5, may be undesirable as there is evidence of a negative, but relatively low, genetic correlation between HH and carcass traits of finishing cattle (Yokoo et al, 2010;Pinheiro et al, 2012). The medium genetic correlation between SC and TOP3 (0.439 ± 0.072) and TOP5 (0.382 ± 0.067) may be improved through the use of high-ranked animals as bulls.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Altarriba et al (2005) evaluated the effect of selection for weight at 210 days of age on carcass traits in Pirenaica animals, which resulted in a greater REA. Pinheiro et al (2012) studied the same lines as used here and reported an increase in the genetic merit of selected Nellore animals (NeS and NeT), with an annual genetic gain of 0.14 and 0.12 cm 2 in REA at 12 and 18 months of age, respectively. Soutello et al (2002) evaluated the development of loin eye area and subcutaneous fat thickness in young bulls (Nellore, ½ Angus-Nellore, ½ Simmental-Nellore, and Canchim) raised in a feedlot system, and reported significant differences in REA at the beginning of the feedlot period between the genetic groups.…”
Section: A B Discussionmentioning
confidence: 92%